Clinical characteristics and assisted reproductive technology outcomes in infertile foreign brides: Comparison with native brides in south Taiwan - Hsin-Ju Chiang; Fu-Jen Huang; Kuo-Chung Lan; Pin-Yao Lin; Pei-Hsun Sung; Fu-Tsai Kung (Elsevier, 2012)
Objective: This study was conducted to determine if differences in clinical characteristics, embryonic development, and pregnancy outcomes exist between infertile foreign and native brides undergoing assisted reproductive technology (ART) treatment in a foreign-bride-immigrating country of Taiwan. Material and Methods: A retrospective, case-control design was use to recruit consecutive infertile women seeking ART treatment for study. The treatment protocol consisted of controlled ovarian hyperstimulation with down-regulation and gonadotropin and ART method with conventional in vitro fertilization or intracytoplasmic sperm injection. Among the 1083 ART treatment cycles, 97 (9%) were from foreign brides and 986 (91%) from native brides. Records of those who received transfer of fresh embryos obtained by using husband sperm for fertilization were collected for analysis. A case-control design with adjustment of bride age was used to select the records of 86 infertile foreign and 172 native brides for the study. Infertility cause, bride age, retrieved oocyte number and maturity, fertilization rate, embryo score, and post-embryo transfer results were assessed. Results: The foreign bride couples had significantly greater infertility due to tubal (36%) and combination (8.1%) factors than native bride couples (20.3% and 4.1%, respectively). Days of gonadotropin stimulation, number of oocytes retrieved, fertilization rate, embryo score, implantation rate, or clinical pregnancy rate, and live birth rate did not differ between the two groups. Conclusion: The cause of infertile foreign bride couples requiring ART treatment had a higher percentage of tubal and combination factors, but similar ART outcomes.